2012
DOI: 10.1007/s11120-012-9785-y
|View full text |Cite
|
Sign up to set email alerts
|

The UV-B photoreceptor UVR8 promotes photosynthetic efficiency in Arabidopsis thaliana exposed to elevated levels of UV-B

Abstract: The UV-B photoreceptor UVR8 regulates expression of genes in response to UV-B, some encoding chloroplast proteins, but the importance of UVR8 in maintaining photosynthetic competence is unknown. The maximum quantum yield of PSII (F (v)/F(m)) and the operating efficiency of PSII (Φ(PSII)) were measured in wild-type and uvr8 mutant Arabidopsis thaliana. The importance of specific UVR8-regulated genes in maintaining photosynthetic competence was examined using mutants. Both F (v)/F(m) and Φ(PSII) decreased when p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 42 publications
1
33
1
Order By: Relevance
“…Our findings, together with the recent description of a complementary role for PHOT in high-light activation of LHCSR3 expression (14), add a tier of regulation through anterograde signaling to the better-known feedback mechanisms operating within the chloroplast. In Arabidopsis, photoperception of UV-B by UVR8 is also important for the maintenance of photosynthetic competence, but the underlying mechanism in higher plants is not clear (35). It will be crucial for agricultural productivity and the biotechnological exploitation of photosynthetic processes to better understand the molecular mechanisms leading to photoprotection and reduced photoinhibition under sunlight and its intrinsic UV-B fraction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings, together with the recent description of a complementary role for PHOT in high-light activation of LHCSR3 expression (14), add a tier of regulation through anterograde signaling to the better-known feedback mechanisms operating within the chloroplast. In Arabidopsis, photoperception of UV-B by UVR8 is also important for the maintenance of photosynthetic competence, but the underlying mechanism in higher plants is not clear (35). It will be crucial for agricultural productivity and the biotechnological exploitation of photosynthetic processes to better understand the molecular mechanisms leading to photoprotection and reduced photoinhibition under sunlight and its intrinsic UV-B fraction.…”
Section: Resultsmentioning
confidence: 99%
“…In both Arabidopsis and Chlamydomonas, some of the UV-B-induced genes encode chloroplast proteins, and UV-B acclimation allows maintenance of photosynthetic efficiency under elevated levels of 35). However, a direct mechanistic link between UVR8 photoreceptor signaling and photoprotection of the photosynthetic machinery has remained unknown.…”
mentioning
confidence: 99%
“…The potential role of UVR8 UV-B signaling in photosynthesis is a current and interesting question. Recent work has begun to address this and has shown in Arabidopsis that UVR8 plays a role in maintaining photosynthetic efficiency under elevated UV-B (Davey et al, 2012). D1 protein levels were also investigated; however, the authors did not observe any difference in the magnitude of D1 protein decrease under UV-B between wild-type and uvr8 plants.…”
Section: Uv-b Acclimation and Tolerance In Chlamydomonasmentioning
confidence: 99%
“…UVR8 regulates additional genes, including those involved with other aspects of metabolism, signaling, and transcriptional regulation. Furthermore, several UVR8-regulated genes encode chloroplast proteins, which likely explains why uvr8 exhibits impaired capacity for photosynthesis compared with wild-type plants under elevated UV-B (Davey et al, 2012). A subsequent microarray analysis (Favory et al, 2009) indicated that several hundred genes are regulated by UVR8 in Arabidopsis seedlings, many in common with those regulated by UVR8 in leaf tissue (Brown et al, 2005).…”
Section: Gene Regulation Underpins Uvr8 Functionmentioning
confidence: 99%